Ethical and legal implications of FDI in or near cultural heritage sites - Charles Ho Wang Mak (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
This Perspective explores the ethical and legal implications of FDI in or near cultural heritage sites, weighing the potential benefits and drawbacks, and suggests measures to promote responsible FDI in this area, such as strengthening safeguards, implementing review processes, and encouraging voluntary codes of conduct to preserve cultural identity.
Keywords: 330